Transforming Teaching and Learning with Artificial Intelligence (AI): Personalized Education, Adaptive Learning, and Intelligent Tutoring Systems - Cittra Juniarni; Akhyar Akhyar; M.Ali Sodikin; Hesta Rafmana; Bashori Bashori (Education Studies and Teaching Journal (EDUTECH), 2024)
This research aims to explore the influence of an adaptive learning system based on Artificial Intelligence (AI) on the development of critical thinking skills (CTS) in various educational contexts. Using a systematic literature review (SLR) approach, this research identifies and analyzes relevant studies published in the last ten years. The analysis results show that the integration of adaptive learning systems supported by AI can improve students' critical thinking skills, with impacts varying depending on factors such as system design, teacher involvement, and educational context. These findings provide valuable insights for educational practitioners and educational technology developers, and recommend future research directions to explore the long-term effects and different cultural contexts on the use of AI technologies for learning.